Situation Report: Hungary, 29 September 1970 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Party Committee Reviews Work of Provincial Daily Strong Security Measures at Budapest Airport Imre Dimeny on the Agricultural Situation The Second Hungarian-British Conference of Economists Hungarian-German-French Co-operation in the Manufacture of Vehicle Engines Hungarian-Italian Economic Relations FAO Conference in Budapest Hungary Urges Early Compensation for Victims of Nazism